EVALUATION OF DEFINITIVE VILLAGE BOUNDARY SEGMENTS IN COMPARISON TO COMPLETE VILLAGE BOUNDARY SEGMENTS FROM THE RESULTS OF COMPLETE SYSTEMATIC LAND REGISTRATION (PTSL): (A Case Study in Tumpakkepuh Village, Bakung District, Blitar Regency) - Mohammad Mansyur; Sayyidatul Khoiridah; Lu’lu’il Munawaroh (Institut Teknologi Sepuluh Nopember, 2025)
The Complete Systematic Land Registration Program (PTSL) aims to provide legal certainty of land ownership through accurate measurement and mapping. One derivative data from PTSL activities is the geometry of village boundaries formed after all plots in the village/sub-district have been measured (complete village). Until 2024, the declaration of complete villages in Blitar Regency was only carried out in Tumpakkepuh Village, which had its definitive village boundaries determined cartometrically in 2018. Evaluation of village boundaries is needed to ensure compliance with the latest PTSL mapping results and support spatial data integration by the One Map Policy. This study evaluates the geometry/spatiality of definitive village boundaries against complete village boundaries in Tumpakkepuh Village, Bakung District, Blitar Regency. The aspects analyzed include differences in segment positions and segment shifts. This study is based on a Geographic Information System using the dissolve and union tools. The results of the geometric evaluation showed that none of the analyzed village boundary line segments overlapped completely or were in the same position. From 7 sample points of segment shifts, it is known that 4 segments shifted out to Pasiraman Village and Lorejo Village and 3 segments entered the complete village boundaries of the Tumpakkepuh Village area. The differences in village boundaries need to be followed up by the Blitar Regency Government by aligning the data through a revision of the determination of definitive village boundaries by adding the plot aspect to the methodology for compiling definitive village boundaries.